Problematika Hukum Pembentukan Undang-Undang Nomor 13 Tahun 2022 Tentang Pembentukan Peraturan Perundang-Undangan - Kurnia, Kana (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2023)
This study aims to find out and analyze first, the implementation of the principle of forming laws and regulations in law number 13 of 2022 concerning the formation of laws and regulations and secondly, the implementation of public participation in the discussion process of law number 13 of 2022 concerning the formation of laws and regulations -invitation. This study uses normative legal research methods with statutory and conceptual approaches. The results of the research conclude that, first, based on the principles of forming laws and regulations, that Law no. 13/2022 only fulfills some of the principles of the formation of laws and regulations as stipulated in Article 5 of Law no. 12/2011 considering that the formation of Law no. 13/2022 seems in a hurry to accommodate the Constitutional Court Decision Number: 91/PUU-XVIII/2020. Second, related to the involvement of public participation in the formation of Law no. 13/2022, the authors conclude that public participation is still minimal, bearing in mind that the transparency of the DPR and the Government in forming laws is only limited to openness of legislation in disseminating information on draft laws without any clarity from the results of public consultations held by the Expertise Body of the Secretariat General of the DPR RI.